2012
DOI: 10.1007/978-1-4614-5441-0_9
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Disease and Diabetes

Abstract: Abstract:Diabetes is cons idered to be a genetica lly and environmenta lly based chronic metabolic and vascular syndro me cau sed by a partial or total insulin defici enc y with alt era tion in the metaboli sm ofl ipids, ca rboh ydrat es and prot eins culm inating wi th di fferent mani festat ion s in differ ent organ isms . In humans hyp erglycem ia is the main con sequence of defects in the secretion and/or action of insulin , and its deregulation can produce secondary lesio ns in various organs , especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
0
11
0
2
Order By: Relevance
“…The etiology of periodontal disease is multifactorial, and is caused by interactions between micro-organisms, a host with some degree of susceptibility and environmental factors (13). According to the current scientific evidence, diabetes is itself a risk factor for periodontitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The etiology of periodontal disease is multifactorial, and is caused by interactions between micro-organisms, a host with some degree of susceptibility and environmental factors (13). According to the current scientific evidence, diabetes is itself a risk factor for periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…According to the current scientific evidence, diabetes is itself a risk factor for periodontitis. The risk of periodontal disease in diabetic patients is 2-3 times that observed in healthy individuals, especially those with inadequate glycemic control as poor glycemic control results in poor immunity (13,14). It has been shown that the advanced glycation end-products (AGE) can lead macrophages to produce high levels of interleukin-1beta (IL-1β) and tumor necrosis factor α (TNF-α) (15).…”
Section: Discussionmentioning
confidence: 99%
“…Symbiosis between diabetes mellitus (DM) and periodontitis is evident in the poor glycemic control seen in patients with CP and increased prevalence and severity of periodontitis seen in patients with DM 4 . Periodontitis has, indeed, been identified as the sixth complication of DM 5…”
mentioning
confidence: 99%
“…These findings suggest that upper-body neck fat may be a unique, pathogenic fat depot. Recent studies have indicated a close correlation of metabolic syndrome and obesity with periodontal disease and with other chronic inflammatory diseases, including type 2 diabetes and CVD (Kuo et al, 2008; Bascones-Martínez et al, 2012; Divaris et al, 2013; Krejci and Bissada, 2013). Whether the relationship between obesity and periodontitis is causal needs to be assessed in future studies.…”
Section: Systems Medicine Of the Oral Microbiomementioning
confidence: 99%